Stabilizing Zn Anode Interface by Simultaneously Manipulating the Thermodynamics of Zn Nucleation and Overpotential of Hydrogen Evolution. (31st August 2022) - Wang, Huibo; Li, Heng; Tang, Yuxin; Xu, Zhu; Wang, Kexuan; Li, Qingyuan; He, Bingchen; Liu, Yi; Ge, Mingzheng; Chen, Shi; Hao, Tianwei; Xing, Guichuan; et al.
Abstract: The uncontrollable dendrite growth, hydrogen evolution, and other side‐reactions, originating from the zinc anode, have severely restricted the practical application of aqueous zinc–ion batteries (ZIBs). To address these challenges, a stable solid‐electrolyte‐interface (SEI) layer is constructed through introducing sericin molecules as an electrolyte additive to modulate the Zn nucleation and overpotential of hydrogen evolution. This SEI layer increases the nucleation overpotential during Zn plating, leading to the finer‐grained, dense, and uniform Zn deposition. Meanwhile, the lower unoccupied molecular orbital molecules in SEI layer have a higher reduction potential than H2 O, inhibiting hydrogen production, and subsequently suppressing the Zn dendritic and interfacial side‐reactions. Consequently, the Zn|Zn symmetric cells with sericin additives exhibit an extremely prolonged cycling lifetime of 4446 h compared with to bare Zn electrode of 53 h at 1.0 mA cm −2 /1.0 mAh cm −2, and a high average Coulombic efficiency of 99.29% under a high cumulative plated capacity of 1.0 Ah cm −2 tested in Zn|Cu cells. Moreover, the assembled full cells using Na2 V6 O16 ·3H2 O cathodes endure 2000 cycles with high capacity retention of 81.7% at 5.0 A g −1 . This study sheds new light on modulating the process of Zn nucleation and overpotential of H2 evolution for durable Zn anode design. Abstract : A stable solid‐electrolyte‐interface layer is rationally constructed through introducing sericin molecular as an electrolyte additive to modulate the Zn nucleation and overpotential of hydrogen evolution through simultaneously controlling: a) the formation of thermodynamically stable zinc nucleus, b) zinc ion diffusion kinetics, and c) the overpotential for hydrogen evolution.